PRACTICALITY ANALYSIS OF MACHINE LEARNING-BASED GEOPHYSICS LEARNING MEDIA IN HIGHER EDUCATION - Abd Mun'im Thariq; Hamsu Abdul Gani; Darmawang Darmawang (Jurnal Vokasi Keteknikan, 2026)
This study aims to analyze the level of practicality of machine learning-based geophysics learning media developed to support learning in higher education. This research uses a Research and Development approach with a focus on evaluating practicality through three stages of trials, namely individual, group, and field trials. The research subjects involved 104 students from UIN Alauddin Makassar and Makassar State University. The research instrument is in the form of an online questionnaire using a 4-point Likert scale that measures aspects of interest, ease of use, quality of instructors, and learning activities. The data was analyzed using descriptive statistics by calculating the average value and categorizing the level of practicality. The results of the study showed that the learning media developed had a high level of practicality, characterized by an increase in scores at each stage of the trial and all aspects were in the practical to very practical category. These findings show that the integration of machine learning is able to increase the ease of use and student involvement in geophysics learning. Thus, this learning media is suitable for use as an innovative alternative in supporting technology-based learning in higher education. This research contributes to the development of artificial intelligence-based learning media that is not only innovative, but also practical and applicative. Further research is suggested to test the effectiveness of media on learning outcomes and develop a more adaptive and integrated system.